Pola Komunikasi Ustadz Komaruddin dalam Membina Akhlak Remaja Masjid Al-Kaafi Kelurahan Babakan Sari Kecamatan Kiaracondong Kota Bandung - Muchlis Dzulhijjah Rachmat; Bambang Saiful Ma'arif; Parihat Kamil (UNISBA Press, 2024)
Abstract. The background to this research problem is how Ustadz Komaruddin uses communication patterns in developing the morals of Al-Kaafi Mosque teenagers. The aim of this research is to determine the Communication Patterns of Ustadz Komaruddin in the Development of Adolescent Morals at the Al-Kaafi Mosque, Babakan Sari Village, Kiaracondong District, Bandung City. This type of research is qualitative, while the research method is descriptive research. The data collection techniques are interviews, observation and documentation. The results of this research still show that the secondary communication pattern from Harold D. Lasswell's formulation is that there are religious figures who discuss religious knowledge, including morals. Various programs from the Mosque Youth Association organization have had an impact in the form of changing teenagers who are often disobedient to rarely disobedient. Those who used to often say harsh words now no longer say harsh words. Those who were previously dating are no longer dating. Abstrak. Latar belakang masalah penelitian ini adalah bagaimana Ustadz Komaruddin menggunakan pola komunikasi dalam membina akhlak Remaja Masjid Al-Kaafi. Tujuan penelitian ini adalah untuk mengetahui Pola Komunikasi Ustadz Komaruddin Dalam Membina Akhlak Remaja Masjid Al-Kaafi Kelurahan Babakan Sari Kecamatan Kiaracondong Kota Bandung. Jenis penelitian ini adalah kualitatif, sedangkan metode penelitian ini adalah studi deskriptif. Teknik pengumpulan datanya adalah wawancara, observasi, dan dokumentasi. Hasil penelitian ini masih terlihat bahwa pola komunikasi sekunder dari formula Harold D. Lasswell yaitu ada Tokoh Agama yang mengatakan perihal Ilmu Agama, termasuk Akhlak. Berbagai program dari organisasi Ikatan Remaja Masjid telah memberikan dampak berupa perubahan remaja yang sering membangkang menjadi jarang membangkang. Mereka yang dahulu sering berkata kasar kini tak lagi berkata kasar. Mereka yang sebelumnya berpacaran kini tidak lagi berpacaran.